PERANAN GURU DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU - Laia, Edison (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2024)
The problem of this research is that students' activeness in learning and student achievement tend to be low. The research objectives are 1) Describe the role of teachers in improving student learning achievement in the Integrated Social Sciences subject class VIII at SMP Negeri 6 Susua. 2) Describe student learning achievements in the Integrated Social Sciences subject class VIII at SMP Negeri 6 Susua. Type of qualitative research. The data sources used are primary and secondary data. Data collection techniques through interviews, observation, documentation. Research results: The role of teachers in improving learning achievement in social studies subjects includes: mastery of subject matter, management of teaching and learning programs, classroom management, use of media, management of learning interactions, conducting evaluations of learning outcomes, and carrying out learning follow-up. Conclusion: The role of social studies teachers in improving student achievement has been carried out well, but there are still many obstacles faced, both from student activities in learning, supporting facilities in the social studies learning process that are inadequate, which has an impact on less than optimal student learning achievement. Suggestions 1) Schools should program extracurricular activities and provide facilities that support learning activities. 2) For teachers, when teaching, teachers should pay attention to their teaching methods or styles which must be in accordance with students' learning styles. A teacher in teaching must prioritize students' understanding of the subject matter being discussed because if students do not understand it will result in low student learning achievement. 3) Students should participate actively in learning activities.